British and Canadian public law in comparative perspective - Loveland, Ian (London [England] : Hart Publishing, 2021)
"This book explores current human rights controversies arising in UK law, in the light of the way such matters have been dealt with in Canada. Canada's Charter of Rights predates the United Kingdom's Human Rights Act by some 20 years, and in the 40 years of the Charter's existence, Canada's Supreme Court has produced an increasingly sophisticated body of public law jurisprudence. In its judgments, it has addressed broad questions of constitutional principle relating to such matters as the meaning of proportionality, the 'horizontal' impact of human rights norms, and the proper role of judicial 'dereference' to legislative decision-making. The court has also considered, more narrowly, specific issues of political controversy such as assisted dying, voting rights for prisoners, the wearing of religious symbols, parental control of their children's upbringing, and the law regulating libel actions brought by politicians. All of these issues are discussed in the book. The contributions to this volume provide detailed analyses of such broad and narrow matters in a comparative perspective, and suggest that the United Kingdom's public law jurisprudence and scholarship might benefit substantially from a closer engagement with their Canadian counterparts."--
Preface -- List of Contributors -- Acknowledgements -- 1. Introduction Ian Loveland -- 2. Assisted Suicide / Carmen Draghici -- 3. Voting Rights for Prisoners / Susan Easton -- 4. The Horizontal Impact of the Charter and the Human Rights Act / Nicholas Bamforth -- 5. Public Law, Private Law, Libel Law / Ian Loveland -- 6. Criminalising Pornography / Gavin Phillipson and Tara Beattie 7. 'Labouring under the Canadian Constitution' Revisited / Keith Ewing -- 8. Wearing Religious Symbols / Nick Hatzis -- 9. Raising Children in Accordance with Unorthodox Religious or Cultural Beliefs / Rachel Taylor -- Index.
Includes index.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web.
Keywords: Public law -- Canada; Constitutional & administrative law; Public law; Constitutional law -- Canada; Constitutional law -- England; Human rights -- Government policy -- Canada; Human rights -- Government policy -- England; Electronic books